A204 PATIENT FACTORS AND STONE FEATURES AS PROGNOSTIC PREDICTORS IN BILIARY STONE LITHOTRIPSY BY SINGLE-OPERATOR CHOLANGIOPANCREATOSCOPY. (4th March 2021) - Sljivic, I; Chahal, D; Trasolini, R; Donnellan, F
Abstract: Background: Single-operator cholangiopancreatoscopy (SOC) is a therapeutic modality for pancreaticobiliary stone disease that is refractory to traditional ERCP. SOC is still considered a relatively novel technology with limited access in many centers and significant associated costs. Thus, it is imperative to understand the influence patient-based factors and ancillary actions have on the outcome of SOC. Aims: We hope to determine if the differences in clinical outcomes amongst cohorts suffice to indicate a re-evaluation of SOC in unfavourable patient populations. We present a series of patients who underwent SOC for biliary stone lithotripsy at a tertiary center with exploratory analysis of factors related to efficacy and adverse events. Methods: This is a retrospective, descriptive case series. Cases were identified via query of the electronic medical record between March 2016 and May 2019. We evaluated patient demographics, past medical history, clinical presentation, disease characteristics, complication rates, and patient outcomes. Descriptive statistics are reported. Results: 25 unique patients underwent a total of 44 SOC procedures. Mean age was 68 (range 22–88). 13 patients were male. 29 procedures involved a stone in the Common Bile Duct (CBD), 5 in the Common Hepatic & Intrahepatic Ducts (CIHD), 4 in the Pancreatic Duct (PD) and 6 in the Cystic Duct (CD). Symptomatic improvement was achieved in 100% of patients. After a single session, 22.7% of procedures resulted in complete clearance and 59.1% of cases led to partial fragmentation. CBD stones however had an 86.2% clearance rate, compared to an 88–91% success rate in literature. The total complication rate was 16% across age and sex groups. The most common complication was bacteremia in 4 (9.1%) cases. Undifferentiated complication rates were highest with CD stones, while bacteremia was most likely with PD stones. A strong trend was noticed between past SOC procedures and increasing ongoing stone burden, with repeat SOC required less often in patient's with fewer past SOC procedures. We further observed poorer fragmentation rates for PD stones and a rising trend for repeat SOCs for proximal CBD stones. Conclusions: SOC is useful against difficult biliary stones and can provide therapeutic relief without theoretical risks associated with surgery and ERCP. While our study was underpowered to provide generalizable statistics, it is one of the few studies that showed the influence certain comorbidities, stone characteristics and age have on the efficacy and safety of SOC. Our data illustrates the relative effect location and stone-size has on fragmentation and complications rates. Poorer outcomes are more frequent in those with systemic comorbidities and previous surgeries, and rates of complications and failed fragmentation are further exacerbated by age. Funding Agencies: None